Kalam On The Go Virtual Immersive Learning Experience finalist AKRI 2022 - Mimi Rabita, Abdul Wahit (UMPSA, 2022)
PUTRAJAYA, 2 September 2022 – Lecturer from the Faculty of Electrical and Electronic Engineering Technology (FTKEE), Universiti Malaysia Pahang (UMP), Dr. Roshahliza M. Ramli was selected for the final stage through the KALAM-ON-THE-GO project for the Virtual Immersive Learning and Blended Innovation category in the Special Award of the Minister of Higher Education: Curriculum Design and Innovative Delivery in 2022 (AKRI 2022).